ANALISIS YURIDIS PERJANJIAN GADAI TANAH MENURUT UNDANG-UNDANG NOMOR. 56/PRP/1960 DI DESA PARASANGANG BERU KECAMATAN TURATEA KABUPATEN JENEPONTO: JURIDICAL ANALYSIS OF LAND PLANT AGREEMENT ACCORDING TO LAW NUMBER. 56 / PRP / 1960 IN PARASANGANG BERU VILLAGE, TURATEA DISTRICT, JENEPONTO DISTRICT - Azikin, Elizah; M. Jafar, Juliati; Taba, Hamzah (Faculty Of Law Bosowa University, 2020)
This inquiry is an purpose for studying, knowing, and understand the implementation of the pawn agreement for agricultural land in Parasangang Beru Village Jeneponto District in accordance based on Law Number 56/Prp/1960 and to understand the mechanism for returning the pawn agreement for agricultural land in the village of Parasangang Beru Village Turatea District Jeneponto Regency in accordance with the provisions of Law Number 56. Prp of 1960 concerning Determination of Agricultural Land Area. The inquiry method used is a type of empirical legal research that is a research conducted on the actual situation or real conditions that occur in the field with the intention to find out and find the facts and data that needed, after the required data is collected then leads to identify problems which then lead to problem solving. This researches uses primary data and secondary data which were carried out in Parasangang Beru Village, Turatea District, Jeneponto Regency and this inquiry was also conducted at the ATR Office of the Jeneponto National Land Agency.Data obtained from observations and interviews and analyzed qualitatively that is descriptive. The results show and indicated that of the implementation of agricultural pawning agreements carried out in the village of Parasangang Beru, Jeneponto Regency were not accordance with the provisions in a Article 7 of Law Number. 56/Prp/1960 concerning the Determination of Agricultural Land Areas. 7 years tend to use customary law and do not use Regulation of the Minister of Agriculture and Agriculture No. 20 of 1963 concerning Guidelines for Settlement of Pawn Problems as implementing regulations in completing agreements for pawn objects for agricultural land in the community.